2021
DOI: 10.5194/aab-64-325-2021
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and meat quality of meat-type guinea fowl fed different commercial diets

Abstract: Abstract. The aim of study was to assess the growth performance, meat quality, and fatty acid composition of meat-type guinea fowl fed balanced commercial diets under two different feeding programs, similar to those for slaughter turkeys and broiler chickens, respectively. A total of 80 4-week-old meat-type guinea fowl divided into two groups (four replicates per group; 10 birds in each replicate) were raised for 14 weeks. One group received commercially available diets in a three-phased program (TM group), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 34 publications
(50 reference statements)
9
14
1
Order By: Relevance
“…Nevertheless, the indigenous birds are smaller in size when compared to their exotic counterparts. While Agwunobi and Ekpenyong [ 55 ] obtained a live weight of 1.5 kg for ‘Golden Sovereign’ Guinea fowl broiler strain under tropical conditions of Nigeria, Batkowska et al [ 56 ] found a range of 2166 ± 42.5–2291 ± 46.9 kg for French commercial set. The differences may be attributed to genetics, age, physiological stage, location and management systems employed by the keepers.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the indigenous birds are smaller in size when compared to their exotic counterparts. While Agwunobi and Ekpenyong [ 55 ] obtained a live weight of 1.5 kg for ‘Golden Sovereign’ Guinea fowl broiler strain under tropical conditions of Nigeria, Batkowska et al [ 56 ] found a range of 2166 ± 42.5–2291 ± 46.9 kg for French commercial set. The differences may be attributed to genetics, age, physiological stage, location and management systems employed by the keepers.…”
Section: Discussionmentioning
confidence: 99%
“…While Agwunobi and Ekpenyong [62] obtained a live weight of 1.5 kg in guinea fowl of 'Golden Sovereign' broiler strain under tropical conditions of Nigeria, Batkowska et al [63] found a range of 2166 ± 42.5-2291 ± 46.9 kg in French commercial set. The differences may be attributed to genetics, age, physiological stage of the birds, location and management systems employed by the poultry keepers.…”
Section: Decision Trees Of the Data Miningmentioning
confidence: 98%
“…This bird species has spread to all continents due its high adaptive capacity. New color varieties of guinea fowl have been developed, and breeding efforts have been made to fully utilize the genetic potential of these birds [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the guinea fowl is not widely produced or consumed in Europe [ 12 ]. This species is characterized by high phenotypic variation; therefore, guinea fowl come in many color varieties and enjoy considerable popularity among amateur breeders in small farms and agritourism farms as a source of meat, eggs, and ornamental feathers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation